2018
DOI: 10.1007/s11064-018-2543-6
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Treadmill Training Promotes Soleus Trophism by Mammalian Target of Rapamycin Pathway in Paraplegic Rats

Abstract: Assisted-treadmill training, may be helpful in promoting muscle mass preservation after incomplete spinal cord injury (SCI). However, biological mechanism involved in this process is still not fully understood. This study investigated the effects of locomotor treadmill training on muscle trophism mediated by protein kinase B (Akt)/mammalian target of rapamycin (mTOR)/p70 ribosomal protein S6 kinase (p70S6K) in paraplegic rats. Adult female Wistar rats underwent an incomplete thoracic SCI induced by compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Interestingly, the authors reported that late training groups had preservation of the motoneurons in the spinal cord and larger muscle fibers area in tibialis anterior muscle; in contrast, the SCI-T7 group had higher lesion volume after locomotor training in comparison with the SCI group, demonstrating that identify a locomotor training starting time after the injury is essential to define the best therapeutic window for rehabilitation. Santo et al (2018) investigated the effects of locomotor treadmill training on muscle tropism mediated by protein kinase B (Akt)/mammalian target of rapamycin (mTOR)/p70 ribosomal protein S6 kinase (p70S6K) in paraplegic adult female Wistar rats underwent an incomplete thoracic SCI induced by compression using an aneurysm clip, and, after 7 days, a 3-week locomotor treadmill training with body weight-support. In particular, trained animals did not show locomotor improvement, but presented an increase in muscle weight and myofiber CSA, confirming the locomotor treadmill training's role in the prevention of soleus muscle hypotrophy in rats with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors reported that late training groups had preservation of the motoneurons in the spinal cord and larger muscle fibers area in tibialis anterior muscle; in contrast, the SCI-T7 group had higher lesion volume after locomotor training in comparison with the SCI group, demonstrating that identify a locomotor training starting time after the injury is essential to define the best therapeutic window for rehabilitation. Santo et al (2018) investigated the effects of locomotor treadmill training on muscle tropism mediated by protein kinase B (Akt)/mammalian target of rapamycin (mTOR)/p70 ribosomal protein S6 kinase (p70S6K) in paraplegic adult female Wistar rats underwent an incomplete thoracic SCI induced by compression using an aneurysm clip, and, after 7 days, a 3-week locomotor treadmill training with body weight-support. In particular, trained animals did not show locomotor improvement, but presented an increase in muscle weight and myofiber CSA, confirming the locomotor treadmill training's role in the prevention of soleus muscle hypotrophy in rats with SCI.…”
Section: Discussionmentioning
confidence: 99%